Kajian Filsafat Ilmu Terhadap Perlindungan Hukum Dan Kompetensi Profesionalisme Pada Jasa Penagihan Anjak Piutang Syariah Pada Studi Kasus PT Matacon Trans Sinergi Dalam Upaya Pembaharuan Perekonomian Masyarakat Muslim Indonesia - Nurinawati Kurnianigsih; Syufa'at (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Financial Technology (Fintech) has an impact on the ease of financial transactions with the rapid emergence of Islamic banking financial institutions. This is proven by the existence of a Sharia Factoring Financing Collection Services Institution in Indonesia. Sharia factoring is the activity of transferring short-term trade receivables of a company along with managing these receivables in accordance with sharia principles. How to apply legal protection and professional competence that must be possessed by Human Resources who have common sense and are good in enforcing sharia financial financing cases. The method used in this research is through a descriptive literature approach. The results and conclusions of this research are to provide an understanding of the public economy regarding legal protection and professional competence in sharia factoring collection services based on the philosophy of science. which has three elements of scientific disciplines that study: Ontology, Epistemology and Axiology. This part of philosophy explains efforts to gain knowledge and then develop it. In this case, sharia economic law can be competent in the renewal of Islamic law based on the philosophy of science.